A complete characterization of microalgal biomass through FTIR/TGA/CHNS analysis: An approach for biofuel generation and nutrients removal. (January 2021) - Arif, Muhammad; Li, Yuxi; El-Dalatony, Marwa M.; Zhang, Chunjiang; Li, Xiangkai; Salama, El-Sayed
Abstract: A comprehensive bio-composition investigation of microalgal species is essential for categorizing their applications. In this study, nutrients uptake followed by complete biomass characterizations, including proximate, ultimate, and bio-compounds (proteins, carbohydrates, and lipids), were performed along with FTIR and TGA/DTG, analyses of four microalgal strains ( Tetradesmus dimorphus GEEL-06, Tetradesmus obliquus GEEL-07, Chlorella sp. GEEL08, and Chlorella sorokiniana GEEL-09). All microalgae species were able to remove 90%–95% nitrogen and phosphorus. T. dimorphus GEEL-06 had highest growth with proteins accumulation of 36.63% and 28.33% of lipids. T. obliquus GEEL-07, Chlorella sp. GEEL08, and C. sorokiniana GEEL-09 accumulated 46.37%, 31.13%, and 39.38% of proteins and 27.94%, 34.61%, and 36.56% of carbohydrates, respectively. FTIR spectra revealed the presence of an alcohol, carboxyl, and amino groups, while biomass pyrolysis showed 67%–80% decomposition. Biodiesel feasibility was confirmed by the presence of 68%–84% C16/C18. These results indicate the potential applications of T. obliquus GEEL-07, C. sorokiniana GEEL-09, and T. dimorphus GEEL-06 /Chlorella sp. GEEL08 for production of higher alcohols, bioethanol, biodiesel/oil for, respectively, along with nutrients removal. Highlights: All the microalgae species were able to remove 90%–95% total nitrogen and phosphorus. The highest accumulated protein 46.37% was achieved with T. obliquus. The highest accumulated carbohydrate 36.56%' was attained with C. sorokiniana. Biochemical, CHNS, TGA, FTIR confirmed microalgae potential as a biofuel feedstock. Biodiesel production feasibility was confirmed by the presence of C16/C18 (68%–84%).